Níveis de treonina para coelhos Nova Zelândia branco em fase de crescimento - Araujo, Ivan Graça (2011)
Four experiments were carried out to verify the inclusion effect of different threonine levels in diets on performance, nitrogen retention and excretion of growing rabbits in the period from 35 to 50 days, and 50 to 70 days old. In the performance period of 35 to 50 days, 120 animals were used, and for the period from 50 to 70 days were used 108 animals. In both experiments the animals were randomly allotted in a randomized design with five levels of total threonine in the diet (0.45, 0.55, 0.65, 0.75 and 0.85), plus a reference diet, totaling six treatments and experimental units consisting of two animals. In the performance test during the period 35 to 50 days of age, the increased levels of Thr in diets did not influence any of the variables. Already in the performance trial conducted from 50 to 70 days of age, the increased levels of Thr in the diets did not influence the performance characteristics. However there was a quadratic effect for dry-casting, in which the lowest value was obtained with the level of 0.75% Thr in the diet. The fat in the carcass decreased linearly with increasing levels of threonine. In tests of nitrogen balance (NB), were used 60 animals in each period, treatments and distributed in a similar design to the performance experiments, a total of six treatments with 10 replicates and one animal each. Each trial lasted 14 NB days and 10 days of adaptation and four days of collection of feces and urine. The experiment of NB, in the period from 35 to 50 days were observed quadratic effects of increasing levels of Thr on the nitrogen excreted in faeces (FN) and nitrogen uptake (NUp), with the lowest FN excretion when the diet had 0, 67% Thr, and for NUp, the highest rate of absorption occurred when the diet had 0.68% of Thr. The other variables were not affected by dietary threonine levels. The experiment of NB, in the period of 50 to 70 days, were observed quadratic effects of increasing levels of Thr on the nitrogen consumed (NC), NC, and NUp, and the NC had the lowest value when the diet had 0.63 % of Thr. In NC, the highest rate of excretion was observed when the diet had 0.61% Thr for the NUp and the lowest rate of absorption occurred when diets owned 0.63% threonine. The other variables were not affected by dietary threonine levels. Based on the results of performance experiments and nitrogen balance in both periods of growth it is concluded that the needs of threonine did not change with age. And the lowest level studied of 0.45% of total threonine in the diet is sufficient to meet the growing needs in both periods.